2014
DOI: 10.1002/smll.201303616
|View full text |Cite
|
Sign up to set email alerts
|

Ordered 2D Colloidal Photonic Crystals on Gold Substrates by Surfactant‐Assisted Fast‐Rate Dip Coating

Abstract: Surfactant induced ordering of 2D and 3D colloidal crystal photonic crystals is possible on metallic substrates by dip‐coating at fast rates (≈1 mm/min). Ordered monolayer opals on conductive gold‐coated silicon substrates behave as a 2D diffraction grating. The method allows high throughput, ordered colloidal crystal formation useful as nanomaterials templates for energy storage or functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 59 publications
(91 reference statements)
0
54
0
Order By: Relevance
“…27,28 There are a number of discrete angles (b) for a given groove spacing (d) where constructive interference occurs between diffracted light, The planar grating equation can be used in calculating the theoretical dispersion of incident light diffracted from a 2D artificial opal.…”
Section: B 2d Opals and Ordered Structures -Planar Dielectric Gratinmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 There are a number of discrete angles (b) for a given groove spacing (d) where constructive interference occurs between diffracted light, The planar grating equation can be used in calculating the theoretical dispersion of incident light diffracted from a 2D artificial opal.…”
Section: B 2d Opals and Ordered Structures -Planar Dielectric Gratinmentioning
confidence: 99%
“…28,[64][65][66][67][68][69][70][71][72][73] Several methods have been investigated towards improving the order of dip-coated colloidal crystals, for example, Khunsin et al investigated the effect of perturbative noise-like acoustic waves on colloidal crystal growth during dip-coating ( Fig. 28,[64][65][66][67][68][69][70][71][72][73] Several methods have been investigated towards improving the order of dip-coated colloidal crystals, for example, Khunsin et al investigated the effect of perturbative noise-like acoustic waves on colloidal crystal growth during dip-coating ( Fig.…”
Section: Colloidal Self-assemblymentioning
confidence: 99%
“…The natural defects that form upon drying after many forms of opal deposition are greater and more numerous than perturbations caused by roughness that are 4-5 orders of magnitude smaller in size (between 0.5-3 nm rms) for our substrates. We have previously investigated the effect of repulsive assembly of the opal template on surfaces with nominal roughness that is similar and as a function of the hydrophobicity and hydrophilicity 52 and it was found that the surface roughness of this magnitude is not a dominant factor for assembly. Effect of sphere size and binary opal templates on inverse opal electrodeposition.-The effect of sphere size in the colloidal opal template [53][54][55][56] on the electrodeposition was also investigated as part of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Dip-coating [36][37][38] Can control thickness of layers by the speed of withdrawal. Gradient in layer thickness.…”
Section: Methods Remarksmentioning
confidence: 99%
“…Dip coating involves the controlled withdrawal of a substrate from a colloidal suspension [36][37][38]. The substrate is vertically held on one end and first submerged into a colloidal suspension.…”
Section: Methods Remarksmentioning
confidence: 99%